PENINGKATAN PERFORMA REPRODUKSI INDUK UDANG WINDU, Penaeus monodon JANTAN TAMBAK MELALUI APLIKASI BAHAN ADITIF DALAM PAKAN MATURASI - Asda Laining; Samuel Lante; Kamaruddin Kamaruddin (Jurnal Perikanan Universitas Gadjah Mada, 2014)
Low mating rate in domesticated tiger shrimp both in pond and controlled tank is probably due to immature spermatozoa because of deﬁ ciency of several micronutrients such as amino acid, certain vitamins and minerals. The purpose of this experiment was to determine the effect of commercial feed additive and to obtain its optimum dose in improving the sperm quality of pond-reared male black tiger. Test diet containing three different levels of feed additive used as treatment at 0 (SX0), 20 (SX20) dan 30 g/kg pakan (SX30). Formulation used in this experiment was standard formulation developed through previous experiment. Two hundreds and ﬁ fty male tiger shrimps were obtained from traditional earthenpond  with weight range from 57 to 99 g and months of age around 8 months (prematuration stage). In order to evaluate the effect of dietary treatments on natural mating rate and fertiled eggs, after 4 months feeding trial, male stocks were mated with wild female tiger shrimp then observed their performances. After 2 moths feeding trial (age of male around 10 months), from 15 male stocks  visually observed, it was still found undevelope spermatophore in each of the tank. Slight development of spermatophore was observed in male stocks fed SX30 around 67% and 53% was found in shrimp fed SX0 and SX20. Furthermore, spermatophore with white color ranged from 13-20% in all dietary treatments. Number of sperm cell in male fed with SX20 was the highest 24 x106 cell and the lowest was found in male fed SX0 yaitu 75 x106 cell. Female maturing without spermatophore in its thelicum was not found in group fed SX0 and female maturing bearing spermatophore was occured in 4 females. Egg fecundity were relative similar in the two groups which was 164,166 eggs obtained in SX0 and 186,489 eggs in SX30. Even though fecundity of the two groups was quite similar, no fertiled egg was spawned by female fed SX0 while in group SX30, 34% of the eggs was fertile and hacthed around 33%. The application of additives as much as 30 g / kg in male tiger shrimp broodstock feed ponds can increase the level of fertilization of eggs by 34% higher than 0% in the feed additive.